A systematic review of the tribes Hyphydrini Sharp and Pachydrini n. trib. (Coleoptera, Dytiscidae) - Biström, Olof; Nilsson, Anders; Wewalka, Günther (Entomologica Fennica, 1997)
Based on a phylogenetic study using adult morphology, the tribe Hyphydrini is redefined as including the following 12 genera: Andex Sharp, Coelhydrus Sharp, Darwinhydrus Shnp, Hydropeplus Sharp, Primospes Sharp, Hyphovatus Wewalka & Biström, Agnoshydrus n. gen. (contains two species: A. laccophiloides (Régimbart) and A. densus n. sp.), Microdytes J. Balfour-Browne, Allopachria Zimmermann, Hyphydrus Illiger, Hovahydrus Biström, and Desmopachria Babington. The two genera Heterhydrus Fairmaire and Pachydrus Sharp are transferred to Pachydrini n. trib. All genera in the two tribes are reviewed including descriptions and check lists. The phylogenetic analysis provided support for the monophyly of each of the genera Allopachria and Desmopachria, whereas that of Microdytes, Hyphydrus and Hovahydrus is considered doubtful. An identification key is provided for the genera and subgenera of both tribes. The following n. comb. are given: Microdytes pasiricus (Csiki, 1938) previously in Hydrovatus and Agnoshydrus laccophiloides (Régimbart, 1888) previously in Microdytes.